Increasing Patient Engagement: Patients’ Responses to Viewing Problem Lists Online - Wright, A.; Feblowitz, J.; Maloney, F.L.; Henkin, S.; Ramelson, H.; Feltman, J.; Bates, D.W. (Applied Clinical Informatics, 2014)
Objective: To characterize the opinions, emotions, and actions taken by patients who viewed their electronic problem list via an online personal health record (PHR).Materials and Methods: An online survey of patients who viewed their problem lists, as maintained by their healthcare provider, in a web-based PHR linked to an electronic health record for the first time.Results: A total 3,649 patients completed the survey, yielding a response rate of 42.1%. Patient attitudes towards the problem list function were positive overall, with 90.4% rating it at least somewhat useful and 86.7% reporting they would probably or definitely use it again. Nearly half (45.6%) of patients identified at least one major or minor problem missing from their list. After viewing the list, 56.1% of patients reported taking at least one action in response, with 32.4% of patients reporting that they researched a condition on the Internet, 18.3% reported that they contacted their healthcare provider and 16.7% reported changing or planning to change a health behavior (patients could report multiple actions). 64.7% of patients reported feeling at least somewhat happy while viewing their problem list, though others reported feeling sad (30.4%), worried (35.7%) or scared (23.8%) (patients could report multiple emotions). A smaller number of patients reported feeling angry (16.6%) or ashamed (14.3%). Patients who experienced an emotional response were more likely to take action.Conclusion: Overall, patients found the ability to view their problem lists very useful and took action in response to the information. However, some had negative emotions. More research is needed into optimal strategies for supporting patients receiving this information.Citation: Wright A, Feblowitz J, Maloney FL, Henkin S, Ramelson H, Feltman J, Bates DW. Increasing patient engagement: Patients’ responses to viewing problem lists online. Appl Clin Inf 2014; 5: 930–942http://dx.doi.org/10.4338/ACI-2014-07-RA-0057
Keywords: Personal medical records; health information technology; patient portal; patient satisfaction; patient survey